Comparison of the MoCA and BEARNI tests for detection of cognitive impairment in in-patients with alcohol use disorders. (1st June 2018) - Pelletier, Stéphanie; Alarcon, Régis; Ewert, Valérie; Forest, Margot; Nalpas, Bertrand; Perney, Pascal
Highlights: The MoCA and the BEARNI are screening tests for cognitive impairment in alcoholics. The BEARNI had very high sensitivity (1.0) but very low specificity (0.04). The MoCA had a very high sensitivity (0.79) and acceptable specificity (0.65). The low BEARNI specificity results from its scoring system. The MoCA seems more appropriate than the BEARNI for use in routine practice. Abstract: Introduction: Screening of cognitive impairment is a major challenge in alcoholics seeking treatment, since cognitive dysfunction may impair the overall efficacy of rehabilitation programs and consequently increase relapse rate. We compared the performance of two screening tools: the MoCA (Montreal Cognitive Assessment), which is widely used in patients with neurological diseases and already used in patients with alcohol use disorder (AUD), and the BEARNI (Brief Evaluation of Alcohol-Related Neuropsychological Impairments), a recent test specifically developed for the alcoholic population. Methods: We compared the sensitivity and specificity of the MoCA and the BEARNI in a sample of AUD patients with and without cognitive impairment assessed by a battery of neuropsychological tests. Results: Ninety patients were included. There were 67 men and 23 women aged 48.9 ± 9.6 years. According to the neuropsychological tests, 51.1% of patients had no cognitive impairment, while it was mild or moderate to severe in 31.1 and 17.8%, respectively. The BEARNI sensitivity was extremely high (1.0), since all patients with cognitive impairment were identified, but its specificity was very low (0.04). The MoCA had a lower sensitivity (0.79) than the BEARNI, but its specificity was significantly better (0.65). A detailed analysis of the BEARNI scores showed a discrepancy between the qualitative and quantitative interpretation of the test which could, at least in part, explain its low specificity. Conclusion: Both the MoCA and the BEARNI are screening tools which identified alcoholic patients with cognitive impairment. However, in routine use, the MoCA appeared to be more appropriate given the low specificity of the BEARNI.